Role of nitric oxide scavenging in vascular response to cell-free hemoglobin transfusion - Sampei, Kenji (2005)
Modified Hb solutions have been developed as O(2) carrier transfusion fluids, but of concern is the possibility that increased scavenging of nitric oxide (NO) within the plasma will alter vascular reactivity even if the Hb does not readily extravasate. The effect of decreasing hematocrit from ~30% to 18% by an exchange transfusion of a 6% sebacyl cross-linked tetrameric Hb solution on the diameter of pial arterioles possessing tight endothelial junctions was examined through a cranial window in anesthetized cats with and without a NO synthase (NOS) inhibitor. Superfusion of a NOS inhibitor decreased diameter, and subsequent Hb transfusion produced additional constriction that was not different from Hb transfusion alone but was different from the dilation observed by exchange transfusion of an albumin solution after NOS inhibition. In contrast, abluminal application of the cross-linked Hb produced constriction that was attenuated by the NOS inhibitor. Neither abluminal nor intraluminal cross-linked Hb interfered with pial arteriolar dilation to cromakalim, an activator of ATP-sensitive potassium channels. Pial vascular reactivity to hypocapnia and hypercapnia was unaffected by Hb transfusion. Microsphere-determined regional blood flow indicated selective decreases in perfusion after Hb transfusion in the kidney, small intestine, and neurohypophysis, which does not have tight endothelial junctions. Administration of a NOS inhibitor to reduce the basal level of NO available for scavenging before Hb transfusion prevented further decreases in blood flow to these regions compared with NOS inhibition alone. In contrast, blood flow to skeletal and left ventricular muscle increased, and cerebral blood flow was unchanged after Hb transfusion. This cross-linked Hb tetramer is known to appear in renal lymph but not in urine. We conclude that cell-free tetrameric Hb does not scavenge sufficient NO in the plasma space to significantly affect baseline tone in vascular beds with tight endothelial junctions but does produce substantial constriction in beds with porous endothelium. The data support increasing the molecular size of Hb by polymerization or conjugation to limit extravasation in all vascular beds to preserve normal vascular reactivity.